2016
DOI: 10.15376/biores.11.3.5949-5960
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Laminated Composite Panels Made from Fast-Growing Species Glued with Mangium Tannin Adhesive

Abstract: Laminated composite is a wood panel constructed from timber pieces then are laminated together. Bio-adhesives such as tannin adhesive are a potential alternative to synthetic adhesives. The purposes of this study were to characterize the chemical makeup of tannin from mangium (Acacia mangium) bark extract and to determine the physical-mechanical properties of the panels made from jabon (Anthocephalus cadamba) and sengon (Falcataria moluccana), and adhesives based on either mangium tannin or methylene diphenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…It was found that density of GLIT composed of densified lamina was higher than density of GLIT composed of undensified lamina, both smoked and unsmoked, as well as density of solid lumber made from the inner part of gewang trunk. The density values of GLIT composed of densified lamina, both smoked (0.61 g/cm 3 ) and unsmoked (0.69 g/cm 3 ), were higher than density of glue laminated panels made from sengon (0.31 to 0.32 g/cm 3 ) and jabon wood (0.44 to 0.47 g/cm 3 ) as studied by Hendrik et al (2016). Sengon and jabon are widely known as two Indonesia fast growing tree species that are commonly used in the wood composite industry in the country.…”
Section: Densitymentioning
confidence: 79%
See 2 more Smart Citations
“…It was found that density of GLIT composed of densified lamina was higher than density of GLIT composed of undensified lamina, both smoked and unsmoked, as well as density of solid lumber made from the inner part of gewang trunk. The density values of GLIT composed of densified lamina, both smoked (0.61 g/cm 3 ) and unsmoked (0.69 g/cm 3 ), were higher than density of glue laminated panels made from sengon (0.31 to 0.32 g/cm 3 ) and jabon wood (0.44 to 0.47 g/cm 3 ) as studied by Hendrik et al (2016). Sengon and jabon are widely known as two Indonesia fast growing tree species that are commonly used in the wood composite industry in the country.…”
Section: Densitymentioning
confidence: 79%
“…It was found that shear strength of GLIT composed of densified lamina was higher than the shear strength of GLIT composed of undensified lamina, both smoked and unsmoked, as well as the shear strength of solid lumber made from the inner part of gewang trunk. The shear strength of GLIT composed of densified lamina, both smoked (3.83 MPa) and unsmoked (4.15 MPa), were higher than shear strength of glue laminated panels made from jabon wood (2.47 MPa), as studied by Hendrik et al (2016). However, shear strengths of GLIT composed of densified lamina were still lower than shear strength of solid lumber made from the outer part of gewang trunk, both smoked (9.08 MPa) and unsmoked (9.01 MPa).…”
Section: Modulus Of Rupturementioning
confidence: 80%
See 1 more Smart Citation
“…dan tancang (Prunilva spp.) (Santoso, 2011;Santoso, Hadi, & Malik, 2012;Hendrik, Hadi, Massijaya, & Santoso, 2016). Zat ekstraktif dari serbuk kayu merbau (Intsia spp.)…”
Section: Pendahuluanunclassified
“…Limbah kayu mengandung tanin dan dapat digunakan sebagai perekat di mana kandungan tanin dari setiap jenis pohon berbeda (Santoso, 1999;Santoso, Malik, & Hadi, 2015). Beberapa penelitian menggunakan tanin dari limbah kayu sebagai perekat seperti limbah kulit kayu mangium (Hendrik, Hadi, Massijaya, & Santoso, 2016;Rachmawati, Sugita, & Santoso, 2018), limbah kulit kayu mahoni (Supriatna, 2017) dan limbah serbuk kayu gergajian merbau (Surya, 2018) menunjukkan nilai emisi formaldehida yang memenuhi standar dan memberikan peluang penggunaan perekat tanin pada pembuatan produk eksterior.…”
Section: Pendahuluanunclassified